1997
DOI: 10.1070/qe1997v027n11abeh001099
|View full text |Cite
|
Sign up to set email alerts
|

Formation and experimental investigation of a gaseous disperse medium of a pulsed chemical H2— F2laser initiated by IR radiation

Abstract: Samples of nominal composition Bi,_._,Pb,Sb,Sr,Ca,Cu,O (x = 0 -0.8, y = 0 -0.3) were prepared and investigated by x-ray, DTA, TG and microprobe analyses. T, was measured by resistive and magnetic (DC susceptibility) methods. The addition of antimony exerted a stabilizing influence on the formation of the 2223 phase, the solubility of Sb being 60.1 mole. The optimal temperatures of t h e formation of the 2223 phases with dinerent Pb a n d S b content are in the range 83W4O"C. Deviation from the optimal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The source of radiation is provided by a pulsed chemical HF laser with the following characteristics [10]: t i = 2.6 µs, λ = 4.2 µm, R = 5 mm, and Θ = 1.5 µs. The thermal and optical properties of particles with due regard for their temperature dependence are found from the respective handbooks.…”
Section: Calculation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of radiation is provided by a pulsed chemical HF laser with the following characteristics [10]: t i = 2.6 µs, λ = 4.2 µm, R = 5 mm, and Θ = 1.5 µs. The thermal and optical properties of particles with due regard for their temperature dependence are found from the respective handbooks.…”
Section: Calculation Resultsmentioning
confidence: 99%
“…The time variation of the pulse is simulated by a continuous piecewise-linear function constructed on the basis of characteristics of a real system [10]. The function simulating the piecewise linear-dependence of laser pulse intensity on time for a system of points t 1 , …, t N with values at the points of F 1 , … F N is written as…”
Section: Model Of Laser Pulsementioning
confidence: 99%
“…As a radiator, we use a pulsed chemical HF laser having the following characteristics [11]: t i = 2.6 µsec; λ = 4.2 µm; R = 1.5 cm; θ = 1.5 µsec. The thermophysical and optical properties of particles were taken from reference books with allowance for their temperature dependence.…”
Section: Gas-dynamic Processes In the Vapor Aureolementioning
confidence: 99%
“…The change in the pulse intensity with time is modeled by the continuous piecewise-linear function formed on the basis of the real system characteristics [11]. The function modeling the piecewise-linear time dependence of the laser-pulse intensity is written on the system of points t 1 , ..., t N with values F 1 , ..., F N as…”
mentioning
confidence: 99%
“…The first experimental results to achieve a photonbranched chain reaction in a two-phase medium were published in [10]. The authors showed that during the injection of a fine-disperse aluminum powder with particle diameters of 0.3 μm covered by thin oxide film into a mixture of F 2 + H 2 + O 2 + He, the system remains stable.…”
Section: Introductionmentioning
confidence: 99%